2020
DOI: 10.3390/ijms21145015
|View full text |Cite
|
Sign up to set email alerts
|

An Intact Cell Bioluminescence-Based Assay for the Simple and Rapid Diagnosis of Urinary Tract Infection

Abstract: Urinary tract infection (UTI) is one of the most common infections, accounting for a substantial portion of outpatient hospital and clinic visits. Standard diagnosis of UTI by culture and sensitivity can take at least 48 h, and improper diagnosis can lead to an increase in antibiotic resistance following therapy. To address these shortcomings, rapid bioluminescence assays were developed and evaluated for the detection of UTI using intact, viable cells of Photobacterium mandapamensis USTCMS 1132 or previously l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The AU formula used for such investigations was AU-Siriraj, which has been documented as one of the most physiologic AU formulas available to date [1]. This physiologic AU formula has been widely used in several recent biomedical studies [2][3][4][5][6][7][8][9][10][11][12]. It is suitable for secretome analysis and the study that avoids contaminations of exogenous proteins (i.e., evaluation of secretory endogenous cytokines/chemokines) [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AU formula used for such investigations was AU-Siriraj, which has been documented as one of the most physiologic AU formulas available to date [1]. This physiologic AU formula has been widely used in several recent biomedical studies [2][3][4][5][6][7][8][9][10][11][12]. It is suitable for secretome analysis and the study that avoids contaminations of exogenous proteins (i.e., evaluation of secretory endogenous cytokines/chemokines) [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…One of those is our previously established formula, AU-Siriraj, which has been proven as one of the most physiologic AU formulas compared with the other protocols [1]. As such, the AU-Siriraj formula has been widely used in several recent studies for disease mechanisms [2], diagnostics [3], biomarker discovery [4], drug delivery [5][6][7][8][9], crystallization and crystal growth [10], biosensors/bioelectronics [11,12], etc. Moreover, a recent study has shown that AU-Siriraj can improve the polarization features of renal tubular epithelial cells using a Transwell system [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically relevant metrics for positive UTI diagnosis (≥10 5 CFU mL −1 ) were reached on a time scale of 20 min. 279…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%
“…On the other hand, MWCBs employ whole bacterial cells, often genetically modified, as miniature reactors to quantify or qualify specific metabolites ( Gui et al., 2017 ). For instance, photogenic bacteria like Photobacterium mandapamensis have been employed to detect pathogens causing urinary tract infections (UTIs), such as E. coli , Proteus mirabilis , S. aureus , and C. albicans ( Reyes et al., 2020 ). In cases where bacteria aren’t naturally photogenic, they can be engineered to express reporter genes like luciferase and green fluorescence protein, generating bioluminescence upon the activation of targeted genes ( Martinez et al., 2019 ; Bazhenov et al., 2023 ).…”
Section: Applications Of Edmentioning
confidence: 99%